Leslie Sansone's walk at home. The big burn, 2 miles of intervals [videorecording (DVD)]. - Sansone, Leslie (Walk at home with Leslie Sansone.)
Walk and jog intervals for big calorie burn. Advanced walkers can take a boosted walk. It's easy to do in small doses, intervals really work to increase calorie burn. Workouts include: a warm up walk to get you ready to move fast; a brisk pace averaging 4 mph, 5 mph and 5.5 mph; mile markers allow you to choose a 1 or 2 mile walk; multi muscle moves - compound exercises give you a bigger calorie burn; a cool down walk and healthy stretch to end.